Developing a Sustainable Integration Model for Sectoral State-Owned Holdings: A Conceptual Framework - Raden Gerald Setiawan Grisanto; Sudarso Kaderi Wiryono; Yos Sunitiyoso (Research Synergy Foundation, 2024)
This paper develops a comprehensive conceptual framework aimed at integrating and synergizing Sectoral State-Owned Holdings (SOHs) to significantly enhance their competitiveness and sustainability. The framework is designed to fill critical gaps in the existing literature by addressing key areas, such as value creation, innovation, and strategic alignment, which are essential for the long-term success of SOHs. One of the primary contributions of this framework is its emphasis on the incorporation of non-economic factors, such as customer satisfaction, community engagement, and environmental stewardship, which are increasingly recognized as vital components of sustainable business practices. The framework also delves into the nuanced impact of government intervention on the performance and strategic orientation of SOHs, exploring how state policies and regulations can either enable or hinder their growth and competitive positioning. By providing a structured approach, this framework enables SOHs to leverage their unique resources and capabilities more effectively, ensuring that they achieve sustainable competitive advantages. Furthermore, the framework underscores the importance of aligning SOH strategies with national economic and social objectives, thereby positioning these entities not only as key drivers of economic growth but also as contributors to broader societal well-being. Ultimately, this paper offers a valuable tool for policymakers, managers, and researchers interested in optimizing the performance and strategic impact of SOHs in a dynamic global economy.